Implementasi Pembelajaran Mendalam terhadap Kemampuan Berpikir Kritis Matematis Siswa - Ratnasari Ratnasari; Nikmah Nurvicalesti; Ami Sulistia Wati (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
The purpose of this study is to examine how deep learning influences students’ mathematical critical thinking skills. In mastering mathematics—which requires reasoning, analysis, and systematic review—critical thinking is essential to address the challenges of the 21st century. This research employs a quasi-experimental design using a pretest-posttest control group model. The subjects of the study were eighth-grade junior high school students, divided into an experimental group and a control group. The main instruments used were a mathematical critical thinking skills test and a learning activity observation sheet. The findings indicate that students who participated in instruction based on a deep learning approach showed a significant improvement in critical thinking skills compared to those who received conventional instruction. Unlike students who underwent standard learning methods, those exposed to deep learning strategies experienced a notable enhancement in their critical thinking abilities. Based on these findings, the implementation of deep learning is recommended more broadly in mathematics classroom instruction.